A GENERAL OVERVIEW OF THE DEVELOPMENT OF THE CIVIL AVIATION SECTOR IN TURKEY - Aksoy, Cenk; Dursun, Omer Osman (My University, 2018)
In parallel with the rapid advances regarding aviation in the world, Turkey has risen to a significant position in the international arena in civil aviation with the records broken in air traffic and the number of passenger, exemplary airport investments in the world, developments in the domestic and international flight network and the regulations made on flight safety and aviation security. Despite all of the adversities experienced in 2016, Turkey, which continues to be spoken throughout the world along with the breakthroughs and projects by evaluating its potential, opportunities and risks, offers the comfort of aviation to the world and its country in a fast and safe way by providing quality service with existing government and private businesses. It can be saidthat Turkey, which has bilateral aviation agreements with 168 countries, is one of the countries with the highest number of flight networks in the world. Turkey, which succeeded to become the member of ICAO Council Member, which sets international aviation rules, in 2016, is among the countries that make contributions in flightsafety and aviation security at the international level. The success of Turkish Airlines, which is Turkey's national airline company and most valuable brand, in the world is also a sign of the importance given to civil aviation in the country. It is thought that the 3rd airport investment in Istanbul, which will enable Turkey to become a centerfor aviation in the world, will make Turkey more powerful in its region and will also provide significant advantages within the context of international strategy as well as economic returns. In this context, the purpose of this study is to summarize Turkey's civil aviation background and to put forward them it in the light of the current data. In addition, it is also aimed to make issues that will make Turkey leader in its region and have a say in the world a current issue and to raise awareness on these issues.
Keywords: Mühendislik; Hava ve Uzay